HUBUNGAN TINGKAT PENGETAHUAN DAN DUKUNGAN SUAMI DENGAN PEMILIHAN ALAT KONTRASEPSI PADA IBU NIFAS DI UPTD PUSKESMAS KISMANTORO - Titik Ariyanti; Aris Prastyoningsih; Tresia Umariyanti (Jurnal Medicare, 2025)
The high birth rate in Indonesia is caused by many factors, one of which is the family planning program that has not been running optimally. Factors that influence the choice of contraceptives include the level of knowledge and support from the husband. If the mother's knowledge about contraceptives is poor and there is no support from the husband, it will affect a person's behavior in choosing a contraceptive, thus affecting the contraceptive used. The purpose of the study was to analyze the relationship between the level of knowledge and support from the husband with the choice of contraceptives in postpartum mothers at the UPTD Kismantoro Health Center. The research design was analytical correlation with a cross-sectional design. The number of samples was 35 respondents with total sampling. Data collection used questionnaires and observation sheets. Univariate, bivariate and multivariate data analysis. Hypothesis testing with t-test and F-test. The results of the study showed that most postpartum mothers had poor knowledge, namely 21 respondents (60%). Did not get support from their husbands, namely 23 respondents (65.7%). The majority of respondents chose long-term contraceptives, namely 12 respondents (34.3%). Conclusion, there is a positive and significant relationship between the level of knowledge and husband's support with the choice of contraceptives in postpartum mothers at the UPTD Kismantoro Health Center partially and simultaneously (Sig. = 0.000).